An Optimal Constraint Programming Approach to the Open-Shop Problem - Malapert, Arnaud; Cambazard, Hadrien; Guéret, Christelle; Jussien, Narendra; Langevin, André; Rousseau, Louis-Martin (Proceedings of the International Conference on Automated Planning and Scheduling, 2013)
This is a summary of the journal article published by Journal on Computing entitled "An Optimal Constraint Programming Approach to the Open-Shop Problem." The article presents an optimal constraint programming approach for the Open-Shop scheduling problem, which integrates recent constraint propagation and branching techniques with new upper bound heuristics. Randomized restart policies combined with nogood recording allow to search diversification and learning from restarts. This approach is compared with the best-known metaheuristics and exact algorithms, and shows better results on a wide range of benchmark instances.